Relativism: Protagoras and Nelson Goodman - Esmaeil Saadati Khamseh (Journal of Philosophical Investigations, 2015)
Discussion of the many faces of relativism occupies a highly prominent place in the epistemological literature. Protagoras in ancient Greece and Nelson Goodman in the modern period are two most notable proponent of relativism. In the present article, I discuss and explain relativistic approaches of this two important relativist. I will first briefly define and review some faces of relativism. Then I will discuss and elaborate Protagorean or true-for-me relativism and Goodman’s radical relativism in turn. I will argue that there are crucial difficulties in Protagorean and radical relativism, and that these difficulties, as the realist philosophers insist, make these two faces of relativism be undefensible. No doubt, these two shapes of relativism have paved the way for anti-realism. In the end, it will appear that Goodman’s radical relativism and so the theory of worldmaking, like Protagorean relativism, suffers from a fatal flaw: the flaw of self-refuting.